KEPERCAYAAN DAN MINAT BELI DI SUB FORUM JUAL BELI www.kaskus.us - Supriyono, Supriyono (Jurnal Riset Ekonomi dan Bisnis, 2010)
The rapid development of e-commerce industry, particularly in Indonesia has become the business spur competition in cyberspace. Internet has changed the boundaries of business processes, eliminating the old paradigm of information technology, and creating a new environment of global online economy. Site www.kaskus.us selling sub forum as an online community forum that offers one means of electronic goods, the automotive, collectibles, fashion items (clothes, shirts, pants, bags, accessories) and others, aiming at world markets and Indonesia in particular Jakarta, Surabaya and Bandung as the access of the majority.Population is the entire online community of customers buying and selling sub-forums www.kaskus.us. Sampling technique using a non-probability sampling with a purposive sampling, selecting respondents who had an order goods online in a website forum. The model used to analyze the data in this study is Structural Equation Modelling (SEM).Based on the results of testing the influence of trust on purchase intention, it can be summed up as follows : Trust has positive influence on Purchase Intention.Keywords : trust, purchase intention